Oxidative degradation of orange II solution using CaMo0.67Cu0.33O3 perovskite: parametric optimization by response surface methodology / Nadhratul Nur Ain Abdul Rahman ... [et al.] - Abdul Rahman, Nadhratul Nur Ain; Zubir, Nor Aida; Alrozi, Rasyidah; Imam Maarof, Hawaiah (Universiti Teknologi MARA, Pulau Pinang, 2022)
This study investigates the optimal operational parameters for oxidative degradation of orange II (OII) in heterogeneous chemical oxidation using CaMo0.67Cu0.33O3 perovskite catalyst. Response surface methodology–central composite design (RSM-CCD) experiments were used to optimize four critical operational parameters: catalyst dosage, initial concentration of OII dye, pH of solution and concentration of H2O2 on the percentage of OII removal. Based on the analysis of variance (ANOVA), the model illustrated a high correlation coefficient (R2) of 0.9941, which suggested that the empirical quadratic model fitted well to the experimental data. The optimal operational parameters were found to be at 0.99 g/L of catalyst dosage, 20.80 mg/L of initial concentration of OII dye, 5.42 pH solution and 0.87 g/L of H2O2 concentration. Interestingly, the experimental OII removal was found to be approximately 91.19% at the suggested optimal conditions. This experimental OII removal value aligns with the predicted value derived from the proposed quadratic model with a difference of 3.98%. Such findings have shown significant global interaction between four critical operational parameters towards OII removal during the heterogeneous chemical oxidation using CaMo0.67Cu0.33O3 perovskite catalyst.